(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To descirbe the characteristics of sharp object injury and idenify factors related to sharp object injuries among medical staff at Duc Giang General Hospital in 2023. Subject and method: A self-administered questionnaire was developed to collect information on demographic characteristics, working environment, knowledge, attitudes and sharp object injury happening in 2023. Descriptive analysis including frequency, percentage, mean and standard deviation was used. Univariate and multivariate logistic regression analysis was used to determine factors associated with the dependent variable (sharp injury) and independent variables (demographic characteristics, working environment, knowledge, and attitudes). Results: The prevelance of sharp injuries in 2023 was 16.8% (70/416). 70.0% (n=291) of particpants had good knowledge and 63.9% (n=266) of particpants had a positive attitude about sharp injury. Univariate regression analysis shows that there is a statistically significant relationship between sharp injury and gender (OR = 2.41; 95%CI: 1.40 - 4.14), department (OR = 3 .37; 95%CI: 1.83 – 6.21), overtime (OR = 1.85; 95%CI: 1.10 – 3.11), night shift (OR = 1.27; 95%CI: 1.14 - 1.39), average number of injections per day (OR = 1.22; 95%CI: 1.09 -1.36), feeling overwhelmed at work work (OR = 3.35; 95%CI: 1.64 – 6.88), feeling stressed due to work ((OR = 3.10; 95%CI: 1.70 - 5.68) and knowledge (OR = 1.79; 95% CI: 1.03 - 2.71). Multivariate logistic regression model showed that there were 2 variables associated with sharp injury including the average number of night shifts per month (OR = 1.21; 95%CI: 1.09 -1.39) and the average number of injections per day (OR = 1.30; 95%CI: 1.15 - 1.49). Conclusion: The prevalence of sharp object injury at Duc Giang General Hospital in 2023 was relatively low. However, this situation can be further improved by assigning appropriate duty schedules and reducing unnecessary injections.